2023
DOI: 10.1371/journal.pone.0283502
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undernutrition and associated factors among adults taking antiretroviral therapy in sub-Saharan Africa: A systematic review and meta-analysis

Abstract: Background Undernutrition (Body Mass Index < 18.5 kg/m2) is a common problem and a major cause of hospital admission for patients living with HIV. Though sub-Saharan Africa is the most commonly affected region with HIV and malnutrition, a meta-analysis study that estimates the prevalence and correlates of undernutrition among adults living with HIV has not yet been conducted. The objective of this study was to determine the pooled prevalence of undernutrition and associated factors among adults living with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…One study from South Africa showed a prevalence of 13% in mixed urban, semi-urban, and rural areas [ 32 ]. A recent meta-analysis from sub-Saharan Africa showed a pooled prevalence of undernutrition of 24% with studies originating mostly from Ethiopia [ 33 ]. Partly, this might be explained by the fact that 49% of patients had a WHO stage 3/4 and 49% had a CD4 cell count <200 cells/mm 3 , both factors associated with undernutrition [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study from South Africa showed a prevalence of 13% in mixed urban, semi-urban, and rural areas [ 32 ]. A recent meta-analysis from sub-Saharan Africa showed a pooled prevalence of undernutrition of 24% with studies originating mostly from Ethiopia [ 33 ]. Partly, this might be explained by the fact that 49% of patients had a WHO stage 3/4 and 49% had a CD4 cell count <200 cells/mm 3 , both factors associated with undernutrition [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Undernutrition studies conducted in Tanzania and Ethiopia among PLWHA reported high levels of nutritional insufficiencies (27.7% and 26%, respectively) in PLWHA. [ 27 , 28 ] Recently, Seid et al [ 29 ] in their meta-analysis review of the prevalence of undernutrition and associated factors among HIV-infected adults taking ART in sub-Saharan Africa reported 23.74%. These figures are relatively high and of serious health concern, given that undernutrition escalates the likelihood of developing opportunistic infections and increased mortality and morbidity.…”
Section: Hiv/aids Infection and Undernutritionmentioning
confidence: 99%
“…These figures are relatively high and of serious health concern, given that undernutrition escalates the likelihood of developing opportunistic infections and increased mortality and morbidity. [ 25 ] According to Seid et al, [ 29 ] reduced CD4 + counts, male gender, advanced disease stage, younger age, delayed initiation of ART, and nonadherence to ART escalate the risk of undernutrition in PLWHA.…”
Section: Hiv/aids Infection and Undernutritionmentioning
confidence: 99%
“…Compared to healthy individuals, adult HIV/AIDS-positive patients require 10% more energy consumption when asymptomatic, 20–30% more when symptomatic, and 30% more when recovering 4 , 6 . In this context, in Sub-Saharan African (SSA) countries, nearly one-fourth (23.7%) of peoples living with HIV/AIDS are undernourished 11 . Similarly, the pooled prevalence of under nutrition among HIV-positive adults in Ethiopia is estimated to be 26% 12 , with a wide variation across regions.…”
Section: Introductionmentioning
confidence: 99%